Relación entre el estado nutricional con la presencia de dermatitis atópica en los niños de la escuela municipal Ángel Felicísimo Rojas - Pozo Rojas, María José (2023)
Malnutrition is related to changes in the skin barrier function, product of specific nutritional deficiencies, which increases the susceptibility to develop atopic dermatitis. Since the two entities constitute a public health problem and that children are the most affected, the present investigation was proposed to establish the relationship between nutritional status and the development of atopic dermatitis. The study had as objectives to characterize according to sociodemographic variables, describe the nutritional status, identify schoolchildren with atopic dermatitis and establish the relationship between nutritional status and atopic dermatitis in children of the Ángel Felicísimo Rojas school during the period September - November 2022. The research had a quantitative, analytical, cross-sectional approach with a prospective vision. It was carried out on the students of the Ángel Felicísimo Rojas municipal school, who met the established selection criteria, whose universe and sample were 179 schoolchildren. Sociodemographic data were obtained, anthropometric values were assessed and the Hanifin and Rajka criteria for atopic dermatitis were applied, with the results that the prevalence of children with inadequate nutritional status was 46.4% (corresponding to underweight, overweight and obesity), at the same time it was observed that the population with atopic dermatitis was 22.9%. In addition, a statistically significant correlation (p=0.001) was observed between inadequate nutritional status and atopic dermatitis. It was concluded that schoolchildren with inadequate nutritional status with atopic dermatitis corresponded to 33.7%